Prevalence of hepatitis B in pregnant women and management of babies born to Hepatitis B positive mother: a criterion based clinical audit - Singh, Alka; Joshi, Suchita; Sharma, Yuba Raj (Journal of Patan Academy of Health Sciences, 2016)
Introductions: This study aims at  identifying the prevalence of Hepatitis B virus infection in pregnant women and adherence to the management of the newborns of these women as per the international guidelines.Methods: This was a cross sectional study conducted at Patan Hospital from January 1, 2008 to December 30, 2014. Prevalence of HBsAg in pregnant women in Patan Hospital and management of babies born to these women, the immunization status, breast feeding status and follow up advice for the babies were studied. These data were analyzed to see whether we were following international guidelines for preventing mother to child transmission of hepatitis B infection.Results: There were total of 58,917 deliveries and 59,438 births during the seven-year study period. During this period, total 148 cases of pregnant ladies with HBsAg positive status were recorded. The prevalence of HBsAg positive case was 0.25% or 1 in every 398 deliveries. Fifty-four babies (87%) received hepatitis B vaccine (HBV) and hepatitis B immunoglobulin (HBIG) within 12 hours of birth. Eight babies (22%) failed to receive HBV and HBIG within 12 hours of birth. Fifty-eight (96%) babies were breastfed after birth. Mother’s HBsAg positive status was not the reason for formula feeding in any of the babies. Follow up HBsAg status was not advised in any of the babies.Conclusions: Patan Hospital seems to be following most of the guidelines in the management of HBV infection in pregnant women, except for checking the HBsAg status of their babies at 9-18 months of age.Journal of Patan Academy of Health Sciences. 2016 Dec;3(2):23-27